NiZn-based ferrite, magnetic core using same, and noise filter

By optimizing the composition ratio of Fe2O3, ZnO, NiO and CuO, NiZn-based ferrite with high Curie temperature and stable composite relative magnetic permeability was prepared, which solved the problems of high production costs and unsatisfactory noise filtering performance, and achieved effective noise filtering in high-frequency and high-temperature environments.

JP7669743B2Active Publication Date: 2025-04-30PROTERIAL LTD

Patent Information

Application Number
JP2021046746
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-28
Filing Date
2021-03-22
Publication Date
2025-04-30
Estimated Expiration
2041-03-22

AI Technical Summary

Technical Problem

The existing NiZn-based ferrite has high production costs, and the Curie temperature and composite relative magnetic permeability are not ideal to the temperature change rate, making it difficult to maintain effective noise filtering performance in high-frequency and high-temperature environments.

Method used

By optimizing the composition ratio of Fe2O3, ZnO, NiO and CuO, NiZn-based ferrites with Fe2O3 content between 47.50 mol% and 48.60 mol%, ZnO content between 29.00 mol% and 30.10 mol%, CuO and NiO content between 5.50 mol% and 6.50 mol% and 14.80 mol% to 18.00 mol% were prepared to ensure that its Curie temperature reaches 160°C or above, and maintain a stable change in the composite relative magnetic permeability within the temperature range of -40°C to 150°C.

Benefits of technology

The high Curie temperature and composite relative magnetic permeability of NiZn-based ferrite are optimized to the temperature change rate, reducing production costs, while maintaining good noise filtering performance in high-frequency and high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669743000014
    Figure 0007669743000014
  • Figure 0007669743000015
    Figure 0007669743000015
  • Figure 0007669743000016
    Figure 0007669743000016
Patent Text Reader

Abstract

To provide a NiZn-based ferrite having excellent productivity and capable of suppressing increase of rate of change of complex relative permeability toward temperature, and a noise filter using the same.SOLUTION: A NiZn-based ferrite contains, on Fe2O3 conversion, 47.50 mol% or over and 48.60 mol% or under of Fe, on ZnO conversion, 29.00 mol% or over and 30.10 mol% or under of Zn, on CuO conversion, 5.50 mol% or over and 6.50 mol% or under of Cu, on NiO conversion, 14.80 mol% or over and 18.00 mol% or under of Ni, with a total amount of Fe2O3, ZnO, NiO, and CuO of 100 mol% and a total amount of Fe2O3 and ZnO of 77.00 mol% or over and 78.50 mol% or under.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a NiZn-based ferrite, and a magnetic core and a noise filter using the same. [Background technology]

[0002] Recent automobiles have adopted vehicle control systems using an in-vehicle LAN (Local Area Network) that performs data communication by differential transmission between multiple electronic control devices. Various electronic components are used in the vehicle control system, and noise filters are used in the signal path to prevent noise leakage in data communication, suppress superposition of external noise on the signal path, and prevent malfunction of in-vehicle devices. The noise filter uses a common mode choke coil in which a conductor is wound around a ferrite core (hereinafter referred to as a magnetic core). There are various configurations of common mode choke coils, such as the one described in Patent Document 1, which uses a drum-shaped core and a plate-shaped core covering it as the magnetic core.

[0003] Noise filters use impedance Z, which is expressed as the product of the complex relative permeability μ of the soft ferrite that makes up the magnetic core and frequency, to remove noise.

[0004] It is generally known that the complex relative permeability μ of soft ferrites has a Snoek limit, where the real part μ' decreases as the frequency increases due to losses caused by magnetic resonance. The higher the complex relative permeability μ of a soft ferrite, the lower the frequency at which the real part μ' begins to decrease. As the real part μ' decreases, the imaginary part μ” increases, peaks, and then decreases. Such complex relative permeability μ is expressed by Equation 1, and in response to changes in the real part μ' and imaginary part μ”, the impedance Z increases exponentially as the frequency increases, and decreases as the real part μ' and imaginary part μ” decrease.

[0005]

number

[0006] For example, CAN (Controller Area Network) is known as a standard for data communication using differential transmission that is widely used as an in-vehicle LAN. Since harmonics of the signal frequency (250 kHz or 500 kHz for CAN) can become radiated noise up to several tens of MHz, noise filters used in the signal path are required to have high impedance in the high frequency band of 10 MHz or more in order to attenuate common mode noise.

[0007] Noise filters are also used in the engine compartments of automobiles, which can become hot. For this reason, in order to be usable in a wide temperature range, for example from -40°C to +150°C, the magnetic transition temperature (Curie temperature Tc) of soft ferrite is required to be at least 150°C higher than the temperature at which it is used, and the temperature dependency of the complex relative permeability μ must be small.

[0008] In response to these requirements, Patent Document 2 discloses a soft ferrite for noise filters that contains Fe, Zn, Ni, Cu, and Ti, with a compound containing Ti dispersed in the grain boundaries of Fe-Zn-Ni-Cu crystals. It states that the Curie temperature is 160°C or higher, the temperature coefficient of magnetic permeability can be suppressed to between -40% and 40%, and an excellent noise filter with stable noise removal performance can be obtained in a wide temperature range from low to high temperatures. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2012-89804 A [Patent Document 2] JP 2011-246343 A Summary of the Invention [Problem to be solved by the invention]

[0010] In Patent Document 2, in order to obtain a grain boundary structure in which a compound containing Ti is dispersed in the grain boundaries, it is necessary to further add TiO2 to a calcined powder of Fe2O3, ZnO, NiO, and CuO powder, pulverize the powder, and mold and sinter the pulverized powder obtained at a predetermined temperature. Since the post-addition of TiO2 is required, the number of production steps, the equipment used, and the types of raw materials are expected to increase in the production of soft ferrite. This may cause problems in providing magnetic cores at low cost. Also, according to Table 2 of Patent Document 2, as the amount of TiO2 increases, the Curie temperature Tc decreases and the temperature coefficient of magnetic permeability on the high temperature side tends to increase, leaving room for further improvement.

[0011] Therefore, an object of the present invention is to provide a NiZn-based ferrite that has a high Curie temperature, is capable of suppressing the rate of change of complex relative permeability with respect to temperature, and is excellent in productivity, and a magnetic core and a noise filter using the same. [Means for solving the problem]

[0012] The first invention is a NiZn-based ferrite containing 47.50 mol% or more and 48.60 mol% or less of Fe, calculated as Fe2O3, 29.00 mol% or more and 30.10 mol% or less of Zn, calculated as ZnO, 5.50 mol% or more and 6.50 mol% or less of Cu, calculated as CuO, and 15.00 mol% or more and 17.00 mol% or less of Ni, calculated as NiO, in which the total amount of Fe2O3, ZnO, NiO, and CuO is 100 mol%, and the total amount of Fe2O3 and ZnO is 77.00 mol% or more and 78.50 mol% or less.

[0013] In the NiZn-based ferrite of the present invention, the Fe content is preferably 47.50 mol % or more and 48.50 mol % or less in terms of Fe2O3, and the Zn content is preferably 29.25 mol % or more and 29.90 mol % or less in terms of ZnO.

[0014] The NiZn-based ferrite of the present invention has a Curie temperature Tc of 160° C. or higher and a complex relative permeability μ 25 It is preferable that the complex relative permeability μ is 800 or more and 1200 or less. 25is the complex relative permeability μ at a frequency of 100 kHz and a temperature of 25°C.

[0015] In addition, the NiZn-based ferrite of the present invention has a temperature Tμ at which the complex relative permeability μ is maximized between 50° C. and 130° C. max It is preferred that the

[0016] In addition, the NiZn ferrite of the present invention has a complex relative permeability μ 25 Complex relative permeability μ max Rate of change of Δμ max It is preferable that the complex relative permeability μ is 40% or less. max is the highest complex relative permeability μ at temperatures from -40°C to 150°C and at a frequency of 100 kHz. In addition, the rate of change Δμ max =(μ max -μ 25 ) / μ 25 × 100(%).

[0017] In addition, in the NiZn-based ferrite of the present invention, when the total amount of Fe, Zn, Ni, and Cu is 100 parts by mass calculated as Fe2O3, ZnO, NiO, and CuO, respectively, it is preferable that Mn is 0.500 parts by mass or less calculated as Mn3O4, Ca is 0.025 parts by mass or less calculated as CaO, and Si is 0.250 parts by mass or less calculated as SiO2.

[0018] Another aspect of the present invention is a magnetic core using the NiZn-based ferrite.

[0019] Another aspect of the present invention is a noise filter using the magnetic core.

[0020] Furthermore, the noise filter of the present invention preferably comprises a first magnetic core having a cylindrical shaft portion and flange portions on both ends of the shaft portion, a plate-shaped second magnetic core disposed between the flange portions of the first magnetic core, and first and second conductive wires wound around the shaft portion of the first magnetic core. Effect of the Invention

[0021] According to the present invention, it is possible to provide a NiZn-based ferrite that has a high Curie temperature, is capable of suppressing the rate of change of complex relative permeability with respect to temperature, and is highly manufacturable, as well as a magnetic core and a noise filter using the same. [Brief description of the drawings]

[0022] [Figure 1] FIG. 2 is a graph showing the relationship between the total amount of Fe2O3 and ZnO and the complex relative permeability μ25 in one embodiment of the NiZn-based ferrite of the present invention. [Diagram 2] FIG. 2 is a diagram showing the relationship between the ZnO amount and the Curie temperature Tc in one embodiment of the NiZn-based ferrite of the present invention. [Diagram 3] FIG. 2 is a graph showing the relationship between the Fe2O3 amount and the rate of change Δμmax in one embodiment of the NiZn-based ferrite of the present invention. [Figure 4] FIG. 2 is a graph showing the relationship between the Fe2O3 amount and the rate of change Δμmin in one embodiment of the NiZn-based ferrite of the present invention. [Diagram 5] FIG. 2 is a diagram showing the relationship between frequency and normalized impedance ZN in one embodiment of the NiZn-based ferrite of the present invention. [Figure 6] FIG. 1 is a diagram showing the relationship between frequency and normalized impedance ZN in a NiZn-based ferrite of a comparative example. [Figure 7] FIG. 1 is an equivalent circuit diagram showing an example of an electronic component in which the NiZn-based ferrite of the present invention is used. [Figure 8] FIG. 2 is a perspective view showing a structure in which a coil and terminals are provided on a magnetic core using the NiZn-based ferrite of the present invention. [Figure 9] 9 is a perspective view showing the external structure of the electronic component shown in FIG. 8. [Figure 10] FIG. 2 is a diagram showing the relationship between the pulverized particle size of the calcined powder and the complex relative permeability μ25 in one embodiment of the NiZn-based ferrite of the present invention. [Figure 11] FIG. 2 is a graph showing the relationship between the pulverized particle size of the calcined powder and the rates of change Δμmax and Δμmin of complex relative permeability in one embodiment of the NiZn-based ferrite of the present invention. [Figure 12] FIG. 2 is a graph showing the relationship between the firing temperature and the rates of change Δμmax and Δμmin of complex relative permeability in one embodiment of the NiZn-based ferrite of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The NiZn-based ferrite according to one embodiment of the present invention and the magnetic core and noise filter using the same will be specifically described below. Unless otherwise specified, the description of one embodiment also applies to other embodiments. Furthermore, the following description is not limiting, and various modifications and additions may be made within the scope of the technical idea of ​​the present invention, and modifications can be made as appropriate.

[0024] 9 is an external perspective view of a noise filter, and the NiZn-based ferrite of the present invention is used, for example, in the magnetic core. The noise filter 10 includes a drum-shaped core (first magnetic core) 21, a plate-shaped core (second magnetic core) 22, a winding 30 provided on the first magnetic core 21, and terminals 31 and 32, with the second magnetic core 22 disposed so as to cover the first magnetic core 21, and is configured to have a closed magnetic circuit structure in which they are adhesively fixed to each other.

[0025] FIG. 8 is a perspective view of the noise filter 10 of FIG. 9 with the second magnetic core 22 removed. The first magnetic core 21 has a shaft portion (not shown) and a first flange portion 25 and a second flange portion 26 at its ends. Two conductor wires are wound helically on the shaft portion of the first magnetic core 21 by bifilar winding to form a first conductor wire 30a and a second conductor wire 30b. Two terminals 31 and 32 are formed on the first flange portion 25 of the first magnetic core 21. Although only a terminal 33 appears on the second flange portion 26, two terminals similar to the first flange portion 25 are formed, and each flange portion has two terminals. One end of the first conductor wire 30a is connected to the first terminal 31, and the other end is connected to a second terminal not shown. One end of the second conductor wire 30b is connected to a third terminal 32, and the other end is connected to a fourth terminal 33.

[0026] Fig. 7 is an equivalent circuit diagram of the noise filter (common mode choke coil) shown in Fig. 9. In the figure, terminal T1 corresponds to the first terminal 31 in the noise filter of Fig. 9. Terminal T2 corresponds to the second terminal (not shown). Terminal T3 corresponds to the third terminal 32, and terminal T4 corresponds to the fourth terminal 33.

[0027] (Composition of NiZn ferrite) The NiZn ferrite used in the magnetic core is composed of 47.50 mol% to 48.60 mol% Fe calculated as Fe2O3, 29.00 mol% to 30.10 mol% Zn calculated as ZnO, 5.50 mol% to 6.50 mol% Cu calculated as CuO, and 14.80 mol% to 18.00 mol% Ni calculated as NiO, with the total amount of Fe2O3, ZnO, NiO, and CuO being 100 mol%, and the total amount of Fe2O3 and ZnO being 77.00 mol% to 78.50 mol%. In addition, unavoidable impurity elements in the raw materials may be included.

[0028] The content of Fe is preferably 47.50 mol % or more and 48.60 mol % or less in terms of Fe2O3. As the amount of Fe2O3 increases, the rate of change Δμ of the complex relative permeability μ described later min and rate of change Δμ max The absolute value of increases, and when it exceeds 48.60 mol%, the desired change rate Δμ min , Δμ max In some cases, the desired rate of change Δμ min , Δμ max The rate of change is Δμ min , Δμ max The absolute values ​​of are 40% or less. Also, if they are less than 47.50 mol%, the complex relative permeability μ 25 is decreased, and the desired complex relative permeability μ 25 In some cases, the desired complex relative permeability μ 25 is 800 or more and 1200 or less. Fe2O3 is more preferably 48.50 mol% or less. Also, it is more preferably 47.80 mol% or more, and even more preferably 48.00 mol% or more.

[0029] The Zn content is preferably 29.00 mol % or more and 30.10 mol % or less in terms of ZnO. If the ZnO content is less than 29.00 mol %, the desired complex relative permeability μ 25 30. If it exceeds 10 mol%, it may not be possible to obtain a Curie temperature Tc of 160°C or higher. max In order to reduce the amount of SiO2, the amount is preferably 29.25 mol % or more, and more preferably 29.90 mol % or less.

[0030] The content of Fe2O3 and ZnO is preferably 77.00 mol% or more and 78.50 mol% or less. By making it 77.00 mol% or more, the complex relative permeability μ 25 can be 800 or more, more preferably 77.30 mol % or more, and preferably 78.40 mol % or less.

[0031] The content of Cu is preferably 5.50 mol % or more and 6.50 mol % or less in terms of CuO. If the content of CuO is less than 5.50 mol % or more than 6.50 mol %, the desired complex relative permeability μ 25 The CuO content is preferably 5.70 mol % or more, and more preferably 6.30 mol % or less.

[0032] The Ni content is preferably 14.80 mol % or more and 18.00 mol % or less in terms of NiO. The NiO content is the remainder obtained by subtracting the total amount of Fe2O3, ZnO, and CuO from the total amount of Fe2O3, ZnO, NiO, and CuO, which is 100 mol %.

[0033] Specific examples of impurity elements include Si, Ca, B, C, S, Cl, Se, Br, P, Te, I, Li, Na, Mg, Al, K, Ga, Ge, Sr, In, Sn, Sb, Ba, Bi, Sc, Ti, Mn, V, Cr, Y, Nb, Mo, Pd, Ag, Hf, Ta, Zr, Co, and Pb. In the present invention, except for Mn, Ca, and Si, the Curie temperature Tc of NiZn-based ferrite and the rate of change Δμ of complex relative permeability with respect to temperature are all min , Δμ maxIt may be included as long as it does not affect the performance, that is, as long as the desired performance is obtained.

[0034] Among the impurity elements contained in the raw materials, Mn, which is contained in large amounts in Fe2O3 as the raw material, is preferably about several thousand ppm in oxide conversion, and the other impurity elements are preferably each limited to about several ppm to several hundred ppm in oxide conversion. In NiZn-based ferrite, Mn is preferably 0.500 parts by mass or less in Mn3O4 conversion, more preferably 0.3 parts by mass or less, per 100 parts by mass of the total amount of Fe2O3, ZnO, NiO, and CuO. Ca is preferably 0.025 parts by mass or less in CaO conversion, and Si is preferably 0.250 parts by mass or less in SiO2 conversion. Among the unavoidable impurities, Na, S, Cl, P, Cr, and B are preferably reduced as much as possible to a total of 0.1 parts by mass or less, and more preferably 0.05 parts by mass or less, in order to prevent abnormal sintering in which insufficient sintering or coarse crystals are generated. In addition, it is preferable that the other unavoidable impurities are all 0.005 parts by mass or less. The total amount of Mn, Ca, and Si in terms of oxides is preferably 0.600 parts by mass or less per 100 parts by mass of the total amount of Fe2O3, ZnO, NiO, and CuO.

[0035] The quantitative analysis of each component of Fe2O3, ZnO, NiO, and CuO can be performed by X-ray fluorescence analysis and ICP emission spectrometry. The qualitative analysis of the contained elements (Fe, Zn, Ni, Cu, Mn, Zr, Sn, P, S, Bi, Mg, Al, Si, Cl, K, Ca, Ti, V, Cr, Co, Pb, etc.) is performed in advance by X-ray fluorescence analysis, and then the contained elements are quantified by a calibration curve method that compares them with a standard sample. In addition, inevitable impurities can be quantified by means of combustion-infrared absorption method, atomic absorption spectrometry, etc. Furthermore, with the exception of Mn, which is contained in large amounts in the raw materials for Fe2O3, and Ca and Si, which are found in large amounts in nature and are likely to cause contamination, other elements are present in small amounts, even if they are contained. Therefore, it is acceptable to calculate the amounts contained in NiZn-based ferrite from the composition ratios based on the values ​​calculated according to the composition ratios of Fe2O3, ZnO, NiO, and CuO from the amounts listed on the inspection sheets for the raw materials for Fe2O3, ZnO, NiO, and CuO.

[0036] (Method of manufacturing NiZn-based ferrite) Powdered compounds (oxides) of the elements Fe, Zn, Ni, and Cu that make up NiZn ferrite are used as raw materials, which are wet-mixed in a specified ratio and then dried to obtain raw powder. The raw powder is calcined at a temperature of 700°C or higher but lower than the sintering temperature to promote spinel formation and obtain a calcined body.

[0037] As the spinel formation progresses, it takes more time to pulverize the calcined body, so the calcination temperature lower than the sintering temperature is preferably at least 100°C lower than the sintering temperature. On the other hand, if the calcination temperature is less than 700°C, the spinel formation is too slow and the time required for calcination becomes too long, so the calcination temperature is preferably 700°C or higher. The calcination temperature is preferably 850°C or higher. If the composition of the calcined body differs (deviations) from the desired composition, the composition may be adjusted by adding compounds of the elements Fe, Zn, Ni, and Cu when the calcined body is pulverized.

[0038] The calcined body is put into a ball mill together with ion-exchanged water and wet-pulverized to obtain a slurry. The calcined body is preferably pulverized until the average particle size of the pulverized powder (measured by air permeability method) is 1.2 μm to 2.5 μm, more preferably 1.5 μm to 2.0 μm. The pulverization time is preferably 0.1 hours to 4.0 hours. If the pulverization time is less than 0.1 hours, the desired pulverized particle size may not be obtained, and if the pulverization time exceeds 4.0 hours, there is a risk of increased inclusion of impurities due to wear of the pulverizing media, container, and other components of the pulverizer.

[0039] A binder such as polyvinyl alcohol is added to the slurry, which is then granulated using a spray dryer and pressure-molded to obtain a molded body of a desired shape. The molded body is sintered in a sintering furnace at a temperature of 1000°C to 1200°C to obtain a sintered body (NiZn-based ferrite magnetic core). The sintering process includes a temperature increase process, a temperature holding process, and a temperature decrease process. The atmosphere in the sintering process may be an inert gas atmosphere or an air atmosphere. In the temperature holding process at a temperature of 1000°C to 1200°C, it is preferable to hold the temperature within a predetermined temperature range for a predetermined time.

[0040] If the average pulverized particle size of the calcined powder is small, the sintering reaction activity is high and densification is easily promoted even at low temperatures, but on the other hand, if the temperature of the sintering furnace is set too high, sintering will be excessive, resulting in coarse crystal structures and making it difficult to produce a dense sintered body with uniform crystal grain size. By setting the average particle size of the pulverized powder to 1.2 μm or more and the sintering temperature in the sintering process to 1000°C or more and 1200°C or less, the complex relative permeability μ 25 and the rate of change of complex relative permeability μ, Δμ min , Δμ max is preferred because it is stable.

[0041] The complex relative magnetic permeability μ, the sintered density ds, and the average crystal grain size d of the obtained sintered body can be measured by the following method. max、 Δμ min The real part μ' and the imaginary part μ” of the complex relative permeability μ are used to calculate the impedance (normalized impedance Z N ) can be calculated.

[0042] (1) Complex relative permeability μ The sintered body is used as a circular magnetic core, and a coil component with a conductor wound around it is used as the evaluation sample. The inductance L m and resistor R m and the resulting inductance L m and resistor R m From this, the complex relative permeability μ, its real part μ', and imaginary part μ″ are calculated using equations 2 to 4.

[0043] (a) The real part μ' of the complex relative permeability μ

number

[0044] (b) Imaginary part μ of complex relative permeability μ”

number

[0045]

number

[0046] The circular core has a rectangular cross section perpendicular to the magnetic path, with an inner diameter of φ20 mm, an outer diameter of φ30 mm, and a thickness of 8 mm. Ae is the effective cross-sectional area of ​​the core (m 2 ), le is the effective magnetic path length of the magnetic core (m), μ0 is the magnetic permeability of a vacuum [4π×10 -7 ](H / m), N is the number of turns of the conductor, f is the frequency (Hz), Lm is the measured inductance (H), and Rm is the measured resistance (Ω). The conductor is an ENIC wire with a wire diameter of φ0.5 mm, and the number of turns N was 20 turns.

[0047] (2) Rate of change of complex relative permeability μ, Δμ max , Δμ min The evaluation sample used to measure the complex relative permeability μ is connected to a measurement jig in a thermostatic chamber. The measurement jig is connected to an LCR meter (4285A), and the temperature of the evaluation sample is changed between -40°C and 150°C, and the inductance L is measured at a frequency of 100 kHz. m and resistor R m Measure the inductance L obtained under the temperature T condition. m and resistor R m From Equation 2 to Equation 4, the complex relative permeability μ T The complex relative permeability μ T is the complex relative permeability μ at temperature T. For example, the complex relative permeability μ 25 is the complex relative permeability μ at a temperature of 25°C. Also, the complex relative permeability μ max is the highest complex relative permeability μ at temperatures from -40°C to 150°C, and Tμ max is the complex relative permeability μ max This is the temperature at which the complex relative permeability μ min is the lowest complex relative permeability μ at temperatures from -40℃ to 150℃, and Tμ min is the complex relative permeability μ min Using the obtained complex relative permeability μ, the rate of change Δμ maxFrom Equation 6, the rate of change Δμ min Calculate.

[0048] The maximum rate of change Δμ on the positive side of complex relative permeability μ max is the absolute value calculated by Equation 5.

number

[0049] The maximum rate of change Δμ on the negative side of the complex relative permeability μ min is the absolute value calculated by Equation 6.

number

[0050] (3) Normalized impedance Z N Frequency response As with the complex relative permeability μ mentioned above, the inductance L at a current of 1 mA was measured using an LCR meter (4285A) at frequencies from 80 kHz to 30 MHz. m and resistor R m and the inductance L m and resistor R m From the above, the real part μ' and the imaginary part μ" of the complex relative permeability μ are calculated using Equation 2 and Equation 3. The obtained real part μ' and imaginary part μ" are used to calculate the normalized impedance Z N The measurement was performed using the test fixture 16085B manufactured by Agilent Technologies.

[0051]

number

[0052] (4) Curie temperature Tc The Curie temperature Tc was determined using a similar sample with an LCR meter according to JIS C2560.

[0053] (5) Sintered density ds The density of the NiZn ferrite sintered body was calculated by the volume weight method from the dimensions and weight. The density of the sintered body was 5.10×10 3 kg / m 3 A sintered body having a low density is considered to be insufficient in sintering, resulting in poor mechanical strength and susceptibility to chipping and cracking.

[0054] (6) Average grain size The sintered body of NiZn-based ferrite was thermally etched at a temperature lower than the sintering temperature, and a scanning electron microscope (SEM) photograph (3000x magnification) of the surface was taken. The observation area of ​​the SEM photograph was 33μm×43μm at 3000x magnification. Three arbitrary straight lines of length L1 were drawn on the SEM photograph, and the number N1 of crystal grains present on each straight line was counted, and the value L1 / N1 was calculated by dividing the length L1 by the number N1 of particles for each straight line, and the sum of the values ​​of L1 / N1 was divided by 3 to obtain the average crystal grain size. Thermal etching may be performed at a temperature at which the crystal grain boundaries can be confirmed, and is typically preferably performed at a temperature about 50°C to 100°C lower than the sintering temperature. If the sintering temperature of the NiZn-based ferrite sintered body is unknown, thermal etching may be started at a low temperature and gradually increased until the crystal grain boundaries can be confirmed. EXAMPLES

[0055] Examples 1 to 21 and Comparative Examples 1 to 9 The Fe2O3 powder, ZnO powder, CuO powder, and NiO powder were weighed so as to obtain NiZn-based ferrite with the composition shown in Table 1, and the raw materials were mixed in a wet state, dried, and calcined at a temperature of 900°C for 1 hour. The calcined bodies obtained were put into a ball mill together with ion-exchanged water and pulverized to form a slurry. A part of the obtained slurry was dried and the average pulverized particle size was evaluated by an air permeability method. The average pulverized particle size was in the range of 1.5 μm to 1.7 μm. Polyvinyl alcohol was added as a binder to the remaining slurry, which was dried and granulated by a spray dryer, and pressed to obtain each circular ring-shaped molded body. The raw materials used were selected so that the amount of Mn in the NiZn-based ferrite was 0.250 parts by mass or less in terms of oxides, including other impurity elements, when the total amount of Fe2O3, ZnO, CuO, and NiO was 100 parts by mass.

[0056] Each compact was sintered at 1100℃ for 2 hours to obtain a ring-shaped NiZn ferrite sintered body with an outer diameter of 30 mm, an inner diameter of 20 mm, and a thickness of 8 mm. The sintering atmosphere was air.

[0057] The density ds, complex relative magnetic permeability μ, real part μ' of complex relative magnetic permeability μ, imaginary part μ' of complex relative magnetic permeability μ, average crystal grain size, Curie temperature Tc, rate of change Δμmin, Δμmax of complex relative magnetic permeability μ, and normalized impedance Z of each NiZn ferrite sintered body. N The results are shown in Table 1 and Figures 1 to 6. In Table 1, the rate of change of complex relative permeability μ is Δμ -40 , Δμ 100 , Δμ 150 is μ 25 The complex relative permeability μ based on T (T = -40℃, 100℃, 150℃) μ 25 μ T When the rate of change Δμ is small and negative, it is indicated with a minus sign. In Figures 1 to 4, examples are indicated with white circles, and comparative examples are indicated with crosses and black squares, and among them, the black squares indicate that the Curie temperature Tc is less than 160°C.

[0058] [Table 1]

[0059] In both the examples and the comparative examples, the density ds of the NiZn ferrite sintered bodies was 5.15×10 3 kg / m 3 The average grain size was in the range of 5μm to 20μm.

[0060] 2 is a diagram showing the relationship between the ZnO content and the Curie temperature Tc of NiZn ferrite. As the ZnO content increases, the Curie temperature Tc decreases, and in Comparative Example 5 to Comparative Example 8, where the ZnO content exceeds 30.10 mol%, the Curie temperature Tc is less than 160° C.

[0061] 3 and 4 are diagrams showing the relationship between the amount of Fe2O3 and the rate of change Δμmax, Δμmin of complex relative permeability μ. max increased rapidly when the Fe2O3 content exceeded 48.60 mol%. min In Comparative Example 5 to Comparative Example 8, in which the Curie temperature Tc is less than 160° C., the complex relative permeability μ min The temperature at which the change occurs is 150°C, while the other evaluation samples are at -40°C. Also, the rate of change Δμ min increased significantly.

[0062] Figure 1 shows the relationship between the total amount of Fe2O3 and ZnO in NiZn-based ferrite and the complex relative permeability μ. As the total amount of Fe2O3 and ZnO increases, the complex relative permeability μ also increases.

[0063] Figures 5 and 6 show the normalized impedance Z of the evaluation sample. N Figure 5 shows the frequency characteristics of μ 25 The evaluation sample of Example 21 having a μ value of 940 was used. 25The results are shown for the evaluation sample of Comparative Example 8 with a resistance of 1480 at temperatures of -40°C, 25°C, 60°C, and 100°C. Note that the upper limit of the measurement temperature is set to 100°C, not 150°C, due to the heat resistance specifications of the test leads (measurement cables) prepared for the measurement. Table 2 also shows the normalized impedance Z N The calculation of μ' and μ" at temperatures of -40℃, 25℃, 60℃, and 100℃ is N Also shown with Z N is the value calculated by formula 7 rounded off to the nearest digit.

[0064] [Table 2]

[0065] In Example 21, the frequency at which μ″ peaks is higher than that in Comparative Example 8, and the normalized impedance Z N In Comparative Example 8, μ' at a temperature of 100°C and a frequency of 30 MHz is almost 0, and μ'' and Z N is lower than that of Example 21, and at a temperature of 150° C., N From this result, μ 25 It is suggested that Comparative Example 8, in which the value exceeds 1200, is not suitable for use as a noise filter at high temperatures.

[0066] Examples 22 to 28 and Reference Examples 1 to 3 Fe2O3 powder, ZnO powder, CuO powder, and NiO powder were weighed so as to obtain NiZn-based ferrite having the composition shown in Example 21 of Table 1, and then wet-mixed, dried, and calcined at a temperature of 900°C for 2 hours. The calcined body obtained was put into an attritor together with ion-exchanged water, and pulverized for 1 minute to 8 hours as shown in Table 3 to obtain a slurry. A part of the obtained slurry was dried and the average pulverized particle size was evaluated by an air permeation method. The average pulverized particle size was within the range of 0.80 μm to 1.85 μm. If there was a deviation in composition as determined by fluorescent X-ray analysis, the raw material was added to adjust the composition to that shown in Example 21. Polyvinyl alcohol was added as a binder to the remaining slurry, which was then dried and granulated using a spray dryer, and the mixture was pressure-molded to obtain ring-shaped compacts.

[0067] Each compact was sintered at 1100℃ for 2 hours to obtain a ring-shaped NiZn ferrite sintered body with an outer diameter of 30 mm, an inner diameter of 20 mm, and a thickness of 8 mm. The sintering atmosphere was air.

[0068] The density ds, complex relative magnetic permeability μ, real part μ' of complex relative magnetic permeability μ, imaginary part μ" of complex relative magnetic permeability μ, and rate of change Δμ of complex relative magnetic permeability μ of each NiZn-based ferrite sintered body were measured or calculated by the above-mentioned method. The obtained results are also shown in Table 3, Figs. 7 and 8. Fig. 7 is a diagram showing the relationship between the pulverized particle size and the complex relative magnetic permeability μ, and Fig. 8 is a diagram showing the relationship between the pulverized particle size and the rate of change Δμ of complex relative magnetic permeability μ. min , Δμ max FIG.

[0069] [Table 3]

[0070] As shown in Fig. 10, when the pulverized grain size of the calcined body exceeds 1.20 μm, the complex relative magnetic permeability μ becomes stable. Also, as shown in Fig. 11, when the pulverized grain size exceeds 1.20 μm, the rate of change of the complex relative magnetic permeability μ Δμ min , Δμ max On the other hand, when the pulverized particle size is 1.20 μm or less, the complex relative magnetic permeability μ decreases, and the rate of change of the complex relative magnetic permeability μ Δμ min , Δμ max has increased.

[0071] Examples 29 to 31 and Reference Examples 4 to 6 Fe2O3 powder, ZnO powder, CuO powder, and NiO powder were weighed so as to obtain NiZn-based ferrite having the composition shown in Example 21 in Table 1, and then wet-mixed, dried, and calcined at a temperature of 900°C for 2 hours. The calcined body obtained was put into an attritor together with ion-exchanged water and pulverized for 0.5 hours to obtain a slurry. Polyvinyl alcohol was added to the obtained slurry as a binder, and the mixture was dried and granulated using a spray dryer, and then pressure-molded to obtain a circular ring-shaped molded body.

[0072] Each compact was sintered at a furnace temperature of 1080°C to 1160°C for 2 hours to obtain ring-shaped NiZn ferrite sintered bodies with an outer diameter of 30 mm, an inner diameter of 20 mm, and a thickness of 8 mm. The sintering atmosphere was air.

[0073] The complex relative permeability μ and the rate of change Δμ of the complex relative permeability μ of each NiNi ferrite sintered body were measured or calculated by the above-mentioned method. The obtained results are also shown in Table 4 and Figure 12. Figure 12 shows the relationship between the sintering temperature and the rate of change Δμ of the complex relative permeability μ. min , Δμ max The firing temperatures shown in Table 4 and Fig. 12 are not the set temperatures of the firing furnace but are the values ​​indicated by a thermal history sensor (Refer Thermo, manufactured by Japan Fine Ceramics Center, a general incorporated foundation).

[0074] [Table 4]

[0075] As is clear from Table 4 and Figure 12, the complex relative permeability μ tends to increase with the firing temperature, and the rate of change of the complex relative permeability μ Δμ max , Δμ min The complex relative permeability μ and the rate of change of the complex relative permeability μ Δμ max , Δμ min If a small crushed particle size that increases sinterability is selected and sintering is performed at a low firing temperature, within a range in which the properties of NiZn ferrite do not decrease, further improvement in the properties of the NiZn ferrite can be expected.

[0076] Examples 32 to 42 and Comparative Examples 10 to 13 The Fe2O3 powder, ZnO powder, CuO powder, NiO powder, Mn3O4 powder, CaCO3 powder, and SiO2 powder were weighed so as to obtain NiZn-based ferrite with the composition shown in Table 5. The Fe2O3 powder, ZnO powder, CuO powder, and NiO powder were wet mixed, then dried and calcined at a temperature of 900 ° C for 1 hour. The calcined bodies obtained were put into a ball mill together with Mn3O4 powder, CaCO3 powder, SiO2 powder, and ion-exchanged water, and pulverized in an attritor to obtain a slurry. A part of the obtained slurry was dried and the average pulverized particle size was evaluated by the air permeability method. The average pulverized particle size was in the range of 1.7 μm to 1.9 μm. Polyvinyl alcohol was added as a binder to the remaining slurry, which was then dried and granulated in a spray dryer, and pressed to obtain each circular ring-shaped molded body.

[0077] Each compact was sintered at 1100℃ for 2 hours to obtain a ring-shaped NiZn ferrite sintered body with an outer diameter of 30 mm, an inner diameter of 20 mm, and a thickness of 8 mm. The sintering atmosphere was air.

[0078] Density ds, complex relative permeability μ, Curie temperature Tc, and rate of change Δμ of complex relative permeability μ for each NiZn ferrite sintered body min , Δμ max was measured or calculated by the above method. The results are shown in Table 6. In Table 6, Fe, Zn, Ni, and Cu are the main components, while Mn3O4, CaO, and SiO2 are listed as minor components.

[0079] [Table 5]

[0080] [Table 6]

[0081] In both the examples and the comparative examples, the density ds of the NiZn ferrite sintered bodies was 5.15×10 3 kg / m3 The average grain size was in the range of 5μm to 20μm.

[0082] In Comparative Examples 10 and 11, where the amount of Mn3O4 is increased to more than 0.500 parts by mass, the complex relative permeability μ on the low temperature side decreases and increases on the high temperature side, and the change rate Δμ of the desired complex relative permeability μ min , Δμ max (absolute value of 40% or less) was not obtained. When the CaO content increases, the rate of change in complex relative permeability μ, Δμ min , Δμ max However, in Comparative Examples 12 and 13, where the amount of SiO2 exceeds 0.250 parts by mass, the complex relative permeability μ decreases and becomes less than 800. In addition, when the amount of SiO2 increases, the complex relative permeability μ increases, but the rate of change Δμ min , Δμ max also increased.

[0083] As explained above, the NiZn-based ferrite is composed of 47.50 mol% or more and 48.60 mol% or less of Fe when calculated as Fe2O3, 29.00 mol% or more and 30.10 mol% or less of Zn when calculated as ZnO, 5.50 mol% or more and 6.50 mol% or less of Cu when calculated as CuO, and 14.80 mol% or more and 18.00 mol% or less of Ni when calculated as NiO, and the total amount of Fe2O3, ZnO, NiO, and CuO is 100 mol%, and the total amount of Fe2O3 and ZnO is 77.00 mol% or more and 78.50 mol% or less, so that the Curie temperature Tc is high and the rate of change Δμ of complex relative permeability μ with respect to temperature is low. min , Δμ max It is possible to make NiZn-based ferrite with small diameter. In addition, since there is no need to make it into a complicated structure, it is also excellent in productivity. Furthermore, noise filters using it can reduce impedance fluctuations caused by temperature changes, and can have good temperature characteristics. [Explanation of symbols]

[0084] 10. Electronic Components 21 First magnetic core 22 Second magnetic core 30 Windings (conductors) 31, 32, 33 Terminals

Claims

1. Fe 2 O 3 47.50 mol% or more and 48.60 mol% or less of Fe, calculated as ZnO, 29.00 mol% or more and 30.10 mol% or less of Zn, 5.50 mol% or more and 6.50 mol% or less of Cu, calculated as CuO, and 14.80 mol% or more and 18.00 mol% or less of Ni, calculated as NiO, 2 O 3 The total amount of ZnO, NiO, and CuO is 100 mol%, Fe 2 O 3 and ZnO in a total amount of 77.00 mol% or more and 78.50 mol% or less, The Curie temperature Tc is 160° C. or higher, and the complex relative permeability μ 25 is 800 or higher and 1200 or lower. NiZn ferrite. Here, the complex relative permeability μ 25 is the complex relative permeability μ at a frequency of 100 kHz and a temperature of 25°C.

2. The NiZn-based ferrite according to claim 1, The Fe is 2 O 3 The NiZn-based ferrite has a Zn content of 47.50 mol % or more and 48.50 mol % or less in terms of ZnO, and Zn is 29.25 mol % or more and 29.90 mol % or less in terms of ZnO.

3. The NiZn-based ferrite according to claim 2, Between 50°C and 130°C, the temperature Tμ at which the complex relative permeability μ is maximum max The NiZn-based ferrite has the following structure.

4. The NiZn-based ferrite according to claim 3, Complex relative permeability μ 25 Complex relative permeability μ max Rate of change of Δμ max The NiZn-based ferrite has a content of 40% or less. However, the complex relative permeability μ max is the highest complex relative permeability μ at a frequency of 100 kHz between −40° C. and 150° C. In addition, the rate of change Δμ max = (μ max -μ 25 ) / μ 25 × 100(%).

5. The NiZn-based ferrite according to any one of claims 1 to 4, The total amount of Fe, Zn, Ni, and Cu is Fe 2 O 3 When calculated as 100 parts by mass of ZnO, NiO, and CuO, Mn is Mn 3 O 4 Ca is 0.025 parts by mass or less in terms of CaO, and Si is 0.500 parts by mass or less in terms of CaO. 2 The NiZn-based ferrite is equivalent to 0.250 parts by mass or less.

6. A magnetic core using the NiZn-based ferrite according to any one of claims 1 to 5.

7. A noise filter using the magnetic core according to claim 6.

8. 8. The noise filter according to claim 7, The magnetic core includes a first magnetic core having a columnar shaft portion and flange portions at both ends of the shaft portion; a plate-shaped second magnetic core disposed between the flanges of the first magnetic core; A noise filter comprising a first conducting wire and a second conducting wire wound around an axis of the first magnetic core.

Citation Information

Patent Citations

  • Soft-magnetic nickel-copper-zinc ferrite material and preparation method thereof

    CN102690109A

  • Nickel-copper-zinc-based ferrite sintered compact having high magnetic flux and low loss and transformer for direct current-direct current converter

    JP1998007454A

  • Ferrite material and ferrite core using the same

    JP2004269316A

  • Common mode filter

    JP2004311560A

  • Ferrite sintered compact and noise filter equipped with the same

    JP2011246343A

Cited By

  • NiZn-BASED FERRITE, MAGNETIC CORE USING THE SAME, AND NOISE FILTER

    JP2025076460A